Exploring senior managers' experiences preparedness to respond to COVID-19: a qualitative study in Iran - Hojatolah Najafi; Zahra Kavosi; Mahnaz Rakhshan; Jalal Karimi; Milad Ahmadi Marzale; Mostafa Bijani; Mahmoudreza Peyravi (BMC, 2023)
Abstract Background Epidemics caused by emerging respiratory viruses are challenging for the health system of most societies, and preparedness of the health system in responding to such epidemics is important. Therefore, the aim of this study was identifying different fields and key issues of the senior managers' experiences preparedness to respond to the COVID-19 epidemic from the Iranian senior managers' point of view. Methods This is a qualitative descriptive study. Eighteen in-depth and semi-structured individual interviews were conducted for data collection. For this purpose, 18 senior managers with work experience in managing the COVID-19 crisis were enrolled in the study using purposive sampling. The collected data were analyzed according to Graneheim and Lundman's approach. Results Analysis of the data resulted in the emergence of five themes and twelve sub-themes. The main themes and sub-themes included: (1) capacity improvement consisting of performance improvement and logistic improvement; (2) resource and infrastructure management including supply and support of human resources, infrastructure improvement, and supply of equipment; (3) an increase in epidemiology capacity including epidemiology improvement and emerging disease surveillance; (4) application of the principles of disaster and emergency management including intra- and extra-organizational interaction management, disaster risk management, and data management; and (5) society resilience increase including improving adaptation skill and maintaining health and social participation. Conclusion The results of this study present the key issues for the management of future emergency situations. Health system managers and policymakers in Iran and other countries should be aware of these key issues and apply them in practice to prepare the health systems to respond to next outbreaks. Indeed, the study results can help policymakers and health system managers to plan to achieve acceptable preparedness for the management of such outbreaks.